Functional Interviewing Was Associated With Improved Agreement Among Expert Psychiatrists in Estimating Claimant Work Capacity: A Secondary Data Analysis of Real-Life Work Disability Evaluations - von Allmen, David Y.; Kedzia, Sarah; Dettwiler, Raphael; Vogel, Nicole; Kunz, Regina; de Boer, Wout E. L. (Frontiers in Psychiatry, 2020)
Objective: Functional evaluations establish functional and work (in-)capacities in the context of disability assessments and are increasingly recommended as a modern technique for work disability assessments. The RELY (Reliable disability EvaLuation in psychiatrY)-studies introduced semi-structured functional interviews in real-life assessments of claimants with mental disorders for evaluating their self-perceived health-related limitations and for investigating the reproducibility of work capacity (WC) estimates. Functional interviews elicit claimants’ self-perceptions about their work-related limitations and capacities in the labour market. This secondary data analysis explored the coverage of work-related key topics in these interviews and investigated whether interviews with high coverage (versus low coverage) of work-related topics resulted in better reproducibility of WC estimates among experts. Methods: Thirty video-taped RELY-assessments underwent a content analysis along a predefined framework for functional interviewing, including the claimant’s self-perceived work limitations and work-related health complaints as centrepieces of functional interviewing. Following transcription, interviews were segmented into coding units. Coding units were allocated to the five steps with 19 key topics of the framework. Enquiry into key topics was ascertained by summing the functional coding units per key topic. Median split grouped interviews into high and low coverage of functional topics and compared them for inter-rater reliability (intraclass correlation coefficient, ICC) and inter-rater agreement (standard error of measurement, SEM). Results: Interviews were broken down in 40’010 coding units, 31% of which addressed functional topics. Enquiries in self-perceived work limitations and work-related health complaints were sparse (coding units medianpsychiatrist between 0 and 1.5, medianpatients between 0 and 9.5). High coverage interviews enquired on more functional topics (68% vs. 42%, p=0.011) and in more depth (36% vs. 16% of functional coding units, p<0.001). Interviews with higher functional coverage reached significantly higher inter-rater agreement in WC ratings among experts (mean difference in SEM, low – high coverage, 7.5%WC, 95% CI 0.2 to 15.1%WC). Inter-rater reliability was low in both groups (ICC, 0.38 versus 0.40). Conclusions: Content analysis showed little enquiry by experts on claimants’ self-perceived activity limitations and work-related capacity. The association between interviews with higher functional coverage and better expert agreement on the claimants’ remaining WC requires confirmation in prospective studie